Enhancing gastroenterology with multimodal learning: the role of large language model chatbots in digestive endoscopy - Qin, Yuanyuan; Chang, Jianming; Li, Li; Wu, Mianhua (Frontiers in Medicine, 2025)
IntroductionAdvancements in artificial intelligence (AI) and large language models (LLMs) have the potential to revolutionize digestive endoscopy by enhancing diagnostic accuracy, improving procedural efficiency, and supporting clinical decision-making. Traditional AI-assisted endoscopic systems often rely on single-modal image analysis, which lacks contextual understanding and adaptability to complex gastrointestinal (GI) conditions. Moreover, existing methods struggle with domain shifts, data heterogeneity, and interpretability, limiting their clinical applicability.MethodsTo address these challenges, we propose a multimodal learning framework that integrates LLM-powered chatbots with endoscopic imaging and patient-specific medical data. Our approach employs self-supervised learning to extract clinically relevant patterns from heterogeneous sources, enabling real-time guidance and AI-assisted report generation. We introduce a domain-adaptive learning strategy to enhance model generalization across diverse patient populations and imaging conditions.Results and discussionExperimental results on multiple GI datasets demonstrate that our method significantly improves lesion detection, reduces diagnostic variability, and enhances physician-AI collaboration. This study highlights the potential of multimodal LLM-based systems in advancing gastroenterology by providing interpretable, context-aware, and adaptable AI support in digestive endoscopy.